A new crocodylid from the middle Miocene of Kenya and the timing of crocodylian faunal change in the late Cenozoic of Africa. (November 2020) - Cossette, Adam P.; Adams, Amanda J.; Drumheller, Stephanie K.; Nestler, Jennifer H.; Benefit, Brenda R.; McCrossin, Monte L.; Manthi, Frederick K.; Nyaboke Juma, Rose; Brochu, Christopher A.
Abstract: Brochuchus is a small crocodylid originally based on specimens from the early Miocene of Rusinga Island, Lake Victoria, Kenya. Here, we report occurrences of Brochuchus from several early and middle Miocene sites. Some are from the Lake Victoria region, and others are in the Lake Turkana Basin. Specimens from the middle Miocene Maboko locality form the basis of a new species, Brochuchus parvidens, which has comparatively smaller maxillary alveoli. Because of the smaller alveoli, the teeth appear to be more widely spaced in the new species. We also provide a revised diagnosis for Brochuchus and its type species, B . pigotti . A phylogenetic analysis supports a close relationship between Brochuchus and tube-snouted Euthecodon, but although relationships among crocodylids appear poorly resolved in the set of optimal trees, this is because Brochuchus and Euthecodon, along with early Miocene " Crocodylus " gariepensis from the early Miocene of Namibia, jointly adopt two distinct positions—either closely related to the living sharp-nosed crocodile ( Mecistops ) or to a group including the living dwarf crocodiles ( Osteolaemus ). Character support for a close relationship with Mecistops is problematic, and we suspect a closer relationship to Osteolaemus will be recovered with improved sampling, but the results here are ambiguous. In either case, Brochuchus is more closely related to living groups not currently found in East Africa. This material helps constrain the timing of crocodylian faunal turnover in the East African Rift Valley System, with endemic lineages largely being replaced by Crocodylus in the middle or late Miocene possibly in response to regional xerification and the replacement of continuous rainforest cover with open grasslands and savannas. UUID: http://zoobank.org/e6f0b219-5f3e-44e5-bdb9-60a4fae8d126